Balancing Ambiguity and Happiness: The Mediating Role of Job Satisfaction in Predicting Turnover Intention: Menyeimbangkan Ambiguitas dan Kebahagiaan: Peran Mediasi Kepuasan Kerja dalam Memprediksi Niat Turnover - B. Medina Nilasari; Asnawi Mashud (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2026)
Turnover intention refers to an individual’s desire to leave an organization. This desire is voluntary and is typically driven by the wish to secure a job that is perceived as better. This phenomenon of turnover intention has serious consequences for an organization’s sustainability, as an increase in employees’ intention to leave can hinder the company’s ability to retain competent employee. This study aims to analyze the influence of role ambiguity and happiness at work on turnover intention, with job satisfaction as a mediating variable. A quantitative approach was employed, with data collected through the distribution of questionnaires and analyzed using Structural Equation Modeling (SEM). The research population consists of employees in the nickel mining and processing industry in North Maluku, with a sample size of 224. The results indicate that role ambiguity has a positive and significant effect on turnover intention and a negative and significant effect on job satisfaction. Conversely, happiness at work does not have a significant effect on turnover intention, although the direction of the relationship is negative, in line with the proposed hypothesis. Nevertheless, happiness at work has a positive and significant effect on job satisfaction. These findings highlight the importance of clearly managing employee roles and enhancing workplace happiness as strategies to improve job satisfaction. However, their impact on reducing turnover intention appears to require a more comprehensive approach.